Immunostimulatory Effect of Coumarin Derivatives before and after Infection of Mice with the Parasite Schistosoma mansoni - Maghraby, Amany; Bahgat, Mahmoud (Arzneimittelforschung, 2004)
Coumarins (pyranobenzopyran derivatives) (coumarin: CAS 91-64-5), organic compounds of known chemotherapeutic importance against bacteria, infectious diseases and tumors, were tested for their immunomodulatory effects. The compounds used in the present study were 1H,9H-3-amino-7-methyl-9-oxo-1-phenylpyran (2,3-h)(l) benzopyran-2-carbonitrile; lH,9H-2-carboxamido-7-methyl-3,9-dioxo-1-phenylpyran (2,3-h)(l) benzopyran; 4H,8H-2-amino-7-bromo-6-methyl-10-nitro-8-oxo-4-(p-nitrophenyl)-pyran (3,2-g) (l) benzopyran-3-carbonitrile; 4H-7-bromo-3-carboxami-do-2,8-dioxo-6-methyl-10-nitro-4-(p-nitrophenyl)2,8-dihydropyran(3,2g)(l) benzopyran. Mice were injected subcuta-neously (0.75 mg/mouse) with each of the compounds for three successive days, then each animal was exposed to 100 Schistosoma mansoni cercariae. The effect on the humoral immune response was detected by measuring immunoglbu-lin G (IgG) levels using enzyme-linked immunosorbent assay (ELISA) against E. coli lysate, soluble worm antigen preparation (SWAP) and cancer bladder tissue homogenates. The reactivity of IgG to E. coli lysate was measured in sera of treated mice before and after infection. However, for SWAP and cancer tissue homogenates the IgG was measured only after infection. Mice given compounds 2, 3 and 4 showed a concentration dependent increase in IgG level against E. coli lysate as compared to untreated uninfected mice. Animals given compounds 3 and 4 followed by S. mansoni infection showed a significant increase (p< 0.05) in IgG level against the same antigen. Moreover, compounds 1, 2 and 4 significantly (p < 0.05) stimulated IgG production when measured against SWAP. Compounds 2, 3 and 4 induced a significant (p < 0.05) IgG response to cancer bladder tissue homogenates as compared to infected control mice. At the cellular level, treatment with compounds 1, 2, 3 and 4 caused a significant increase (p < 0.05) in the mean percentage of CD4+-T cells as compared with normal control, whereas, compounds 1, 2 and 3 stimulated a significant increase (p < 0.05) in the mean percentage of CD8+-T cells. Six weeks post-infection compounds 3 and 4 induced a significant stimulation (p< 0.05) in the mean number of both CD4+ and CD8+-T cells. The study showed that the compounds used have an immunomodulatory effect at both humoral and cellular levels.
Keywords: CAS 91-64-5; Coumarin, derivatives; Immunostimulants; Pyranobenzopyran derivatives, effects on cellular and humoral immune responses, mouse; Schistosoma mansoni